2019
DOI: 10.3390/vaccines7040193
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Avian Influenza H5 Hemagglutinin Fused with the A Subunit of Type IIb Escherichia coli Heat Labile Enterotoxin Elicited Protective Immunity and Neutralization by Intranasal Immunization in Mouse and Chicken Models

Abstract: Highly pathogenic avian influenza viruses are classified by the World Organization for Animal Health (OIE) as causes of devastating avian diseases. This study aimed to develop type IIb Escherichia coli heat-labile enterotoxin (LTIIb) as novel mucosal adjuvants for mucosal vaccine development. The fusion protein of H5 and LTIIb-A subunit was expressed and purified for mouse and chicken intranasal immunizations. Intranasal immunization with the H5-LTIIb-A fusion protein in mice elicited potent neutralizing antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The direct fusion of the CT A1 subunit with influenza A matrix protein 2 (M2e) and an immunoglobulin binding D domain (DD) (CTA1-M2e-DD) has been shown to confer a broad range of protective immunity against homologous and heterologous influenza A viruses (37)(38)(39). We have previously reported that a direct fusion of the type IIb LT A subunit (LTA) with influenza hemagglutinin via intranasal immunization induced both systemic and mucosal immunity against H5N1 infections in mice and chickens (40). In this study, we used the direct fusion of the type IIb LTA with RBD of SARS CoV-2 S protein (RBD-LTA) as an intranasal vaccine candidate and evaluated for its elicitation of systemic and mucosal and systemic immune responses in BALB/c mice and golden hamsters.…”
Section: Nasal Immunization Can Elicit Both Systemic and Mucosal Immu...mentioning
confidence: 99%
“…The direct fusion of the CT A1 subunit with influenza A matrix protein 2 (M2e) and an immunoglobulin binding D domain (DD) (CTA1-M2e-DD) has been shown to confer a broad range of protective immunity against homologous and heterologous influenza A viruses (37)(38)(39). We have previously reported that a direct fusion of the type IIb LT A subunit (LTA) with influenza hemagglutinin via intranasal immunization induced both systemic and mucosal immunity against H5N1 infections in mice and chickens (40). In this study, we used the direct fusion of the type IIb LTA with RBD of SARS CoV-2 S protein (RBD-LTA) as an intranasal vaccine candidate and evaluated for its elicitation of systemic and mucosal and systemic immune responses in BALB/c mice and golden hamsters.…”
Section: Nasal Immunization Can Elicit Both Systemic and Mucosal Immu...mentioning
confidence: 99%